Regulatory Enforcement Mechanisms Influencing Corporate Financial Reporting Behavi (gjstudies, 2020)
This research investigates the differential impacts of formal versus informal regulatoryenforcement mechanisms on corporate financial reporting behavior, proposing a novel theoretical framework that integrates institutional theory with behavioral economics. Whileexisting literature predominantly focuses on formal sanctions, this study uniquely examines how informal mechanisms—including regulatory reputation, peer benchmarkingdisclosures, and public enforcement narratives—shape reporting decisions through psychological and social channels. We develop an original methodology combining computational text analysis of regulatory communications with a quasi-experimental design usinga proprietary dataset of enforcement actions from 1998 to 2004. Our analysis revealsthat informal mechanisms account for approximately 40% of the variance in reportingquality improvements following enforcement actions, a substantially larger effect thanpreviously documented. Furthermore, we identify a counterintuitive ’deterrence saturation’ point beyond which increased formal penalties yield diminishing returns, whileinformal mechanisms continue to exert influence. The findings challenge conventionalenforcement models and offer a more nuanced understanding of regulatory efficacy. Thisresearch contributes to the accounting, regulatory, and behavioral literature by providinga comprehensive framework for analyzing enforcement ecosystems and offering evidencebased recommendations for optimizing regulatory strategy in evolving financial markets.